2019
DOI: 10.1021/jacs.8b12872
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin Is a Functional Binding Protein for Salinomycin in Neuroblastoma Stem Cells

Abstract: The aim of this study is to illuminate a novel therapeutic approach by identifying a functional binding target of salinomycin, an emerging anticancer stem cell (CSC) agent, and to help dissect the underlying action mechanisms. By utilizing integrated strategies, we identify that nucleolin (NCL) is likely a salinomycin-binding target and a critical regulator involved in human neuroblastoma (NB) CSC activity. Salinomycin markedly suppresses NB CD34 expression and reduces CD34+ cell population in an NCL-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 46 publications
2
39
0
1
Order By: Relevance
“…Finally, a recent study identified nucleolin as the functional binding target of Sal. The drug inhibited the transcription of the nucleolin gene (NCL) and led to a suppression of downstream CD34 gene expression [70], which was also shown in our RNA-seq data.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, a recent study identified nucleolin as the functional binding target of Sal. The drug inhibited the transcription of the nucleolin gene (NCL) and led to a suppression of downstream CD34 gene expression [70], which was also shown in our RNA-seq data.…”
Section: Discussionsupporting
confidence: 85%
“…CD44 exists as a large family of isoforms, produced by the alternative splicing of up to 20 exons, and CD44v6, in particular, is required for CSCs migration and generation of metastatic tumors 44 . Tumor spheres co-expressed other NB stem cells marker proteins such as CD114 23,24 and NCL 25 and the nucleolar antigens NPM1 40 and PES1 42 , as well as GPC2, that is an oncoprotein strongly candidate to be an immunotherapeutic target in NB 41 . While studying embryonic antigens in neurospheres, we discovered that they expressed the stem cell marker N-Cadherin and the embryonic morphogen Nodal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[100,101] Furthermore,western blots and microscopy experiments revealed features of lysosomal degradation of iron-binding proteins that led to lysosomal and lipid reactive oxygen species (ROS) and lysosomal membrane permeabilization. [104] Thei nv itro studies performed in the 1970s,o nw hich we base the use of ionophores as cell biological tools,d on ot capture the complexity of cellular systems having ap lethora of ion gradients that are often interrelated. [102,103] Interestingly,t he Rodriguez lab found that cell death by salinomycin could be blocked by the ferroptosis inhibitors N-acetylcysteine,ferrostatin-1, and deferoxamine,w hich made the team conclude that salinomycin induced ferroptosis to selectively target CSCs.C ollectively,t hese studies demonstrate that chemical derivatization of ionophores can enable the discovery of critical mechanistic details.V ery recently,n ucleolin was identified as adirect and functionally relevant binding protein of salinomycin in neuroblastoma cell lines.T his interesting observation may shed additional light on how salinomycin exerts its inhibitory effects against CSCs and it furthermore underscores that cellular activities not involving ion transport are entirely possible for the carboxyl polyether ionophores.…”
Section: Methodsmentioning
confidence: 99%